2020
DOI: 10.1111/tpj.14787
|View full text |Cite|
|
Sign up to set email alerts
|

Genotypic and phenotypic characterization of a large, diverse population of maize near‐isogenic lines

Abstract: This is the author manuscript accepted for publication and has undergone full peer review but has not been through the copyediting, typesetting, pagination and proofreading process, which may lead to differences between this version and the Version of Record. Please cite this article as

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
24
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(24 citation statements)
references
References 37 publications
0
24
0
Order By: Relevance
“…NILs with introgressions across the centromeric region of chromosome 8 overlapped two QTL for resistance to NLB, including qNLB8.06, which overlaps the Ht2 and Htn resistance loci (Chung et al 2010;Hurni et al 2015). Co-localized QTL regions for resistance to NLB between this nNIL study and the larger nNIL library (Morales et al 2020) were identified near qNLB6.05 and in overlapping qNLB8.05 regions. Differences in the disease phenotyping environments, genotyping and analysis methodologies, as well as nNIL library composition maybe have contributed to the limited concordance between the results from the two nNIL libraries.…”
Section: Description and Utility Of The Nnil Library For Dissection Omentioning
confidence: 71%
See 4 more Smart Citations
“…NILs with introgressions across the centromeric region of chromosome 8 overlapped two QTL for resistance to NLB, including qNLB8.06, which overlaps the Ht2 and Htn resistance loci (Chung et al 2010;Hurni et al 2015). Co-localized QTL regions for resistance to NLB between this nNIL study and the larger nNIL library (Morales et al 2020) were identified near qNLB6.05 and in overlapping qNLB8.05 regions. Differences in the disease phenotyping environments, genotyping and analysis methodologies, as well as nNIL library composition maybe have contributed to the limited concordance between the results from the two nNIL libraries.…”
Section: Description and Utility Of The Nnil Library For Dissection Omentioning
confidence: 71%
“…The nNIL library described in this paper is part of a community resource developed by Syngenta as a tool for dissection of important traits (Gandhi et al 2001;Morales et al, 2020) and available upon request from the International Maize and Wheat Improvement Center (CIMMYT). We describe a subset of a larger population of NILs derived from 18 donor parents (consisting of founder lines in the NAM population) and backcrossed to B73, that were initially selected to harbor introgressions around known QTL for resistance to NLB.…”
Section: Description and Utility Of The Nnil Library For Dissection Omentioning
confidence: 99%
See 3 more Smart Citations